Sistem Rekomendasi Ukuran Baju Pada E-commerce Dengan Metode Naive Bayes - suwoto, Yogo Mahardika; Yusrida Muflihah (Jurnal Mahasiswa Teknik Informatika, 2024)
The dress size recommendation system has become an important feature in e-commerce applications to help users choose the right size when shopping online. Therefore, we introduce a dress size recommendation system that uses the Naive Bayes algorithm for e-commerce applications. The dress size recommendation system using the Naive Bayes algorithm in this e-commerce application is expected to improve the user's online shopping experience. After the model is trained, when a user accesses an e-commerce application and searches for clothing products, the system will use the information collected from the user such as gender, height, weight, chest circumference and usual clothing sizes as input features. Then, the Naive Bayes model will calculate the probability that a user with these characteristics will choose a certain shirt size. Keywords - Recommendation System, Naïve Bayes, e-commerce, dress sizes.